2002
DOI: 10.1055/s-2002-35698
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Therapy for Chronic Hepatitis B

Abstract: Two agents are currently approved for the treatment of chronic hepatitis B: interferon alfa and lamivudine. Each agent has inherent limitations for use in the treatment of chronic hepatitis B. Interferon alfa is effective in a small number of patients and has serious side effects that limit its tolerability. The efficacy of lamivudine is limited by the emergence of drug-resistant hepatitis B virus (HBV) mutants, restricting its utility as a long-term therapy for chronic hepatitis B. As a result, a large propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
0
17
2
Order By: Relevance
“…Same our study, Pradeep et al [20] in their study expressed that 6 month medication by Adefovir Dipivoxil and Lamivudine can significantly decrease ALT level and viral load in HBV patients. In their study, no significant difference was observed between Adefovir Dipivoxil and Lamivudine groups to ALT level and HBeAg seroconversion after 6 month therapy [18], but we have a significant decrease ALT level in Lamivudine group after 6 month. Furthermore, in this study after 12 month, Lamivudine significantly better than Adefovir Dipivoxil and Tenofovir Disoproxil Fumarate was able to normalized ALT level.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Same our study, Pradeep et al [20] in their study expressed that 6 month medication by Adefovir Dipivoxil and Lamivudine can significantly decrease ALT level and viral load in HBV patients. In their study, no significant difference was observed between Adefovir Dipivoxil and Lamivudine groups to ALT level and HBeAg seroconversion after 6 month therapy [18], but we have a significant decrease ALT level in Lamivudine group after 6 month. Furthermore, in this study after 12 month, Lamivudine significantly better than Adefovir Dipivoxil and Tenofovir Disoproxil Fumarate was able to normalized ALT level.…”
Section: Discussioncontrasting
confidence: 62%
“…However, viral gene mutation that laid to Lamivudine resistance is event frequently [18]. Recently, Adefovir Dipivoxil, a prodrug of Adefovir, was approved for used in chronic hepatitis B patients [14,19,20].…”
Section: Adefovir Dipivoxil Tenofovir Disoproxil Fumarate or Lamivudmentioning
confidence: 99%
“…Recently, lamivudine was approved for the treatment of chronic HBV infection in many regions of the world. Although convenient and well-tolerated, lamivudine's efficacy rate was similar to interferon and prolonged administration of lamivudine was associated with development of resistance [24][25][26][27][28][29][30] . New agents, such as adefovir dipivoxil, offered a promise either alone or in combination with lamivudine in the treatment of individuals who were 'treatment naïve' have developed lamivudine resistance [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, nucleoside analogues, such as lamivudine and adefovir, are new treatment options that result in a rapid decrease in serum HBV DNA, as well as an improvement of liver histology. Unfortunately, these agents are associated with a rapid rate of relapse and selection of resistant viral variants [5,6] . As such, novel therapeutic alternatives are continually being explored.…”
Section: Introductionmentioning
confidence: 99%